The beauty of mathematics in Indonesian culture: An impactful and meaningful context in number patterns learning - Khasanah, Binti Anisaul; Prahmana, Rully Charitas Indra; Adiputra, Sofwan; Arnal-Palacián, Mónica (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2025)
The integration of cultural heritage into mathematics learning remains underexplored, particularly in the context of Indonesian traditional arts. Existing mathematics curricula often overlook the potential of local cultural artifacts to contextualize abstract mathematical concepts. This study addresses this gap by investigating the mathematical structures embedded within Batik Lampung motifs, highlighting their novelty in representing numerical patterns through culturally significant designs. The primary aim of this research is to explore and analyze mathematical pattern concepts—specifically odd and even arithmetic sequences, square numbers, rectangular numbers, and constant sequences—within the Siger, Gajah, Pucuk Rebung, Sembagi, and Kapal motifs of Batik Lampung, while also uncovering their underlying philosophical meanings. Employing a qualitative ethnographic approach, the study collected data through visual documentation, direct observation, semi-structured interviews, and literature review. The findings reveal the presence of arithmetic sequences, square and rectangular number patterns, and constant sequences, each reflecting cultural values such as sustainable growth, balance, perfection, and continuity. These results underscore the potential of Batik Lampung as a meaningful and contextual medium for mathematics instruction. This study contributes to the development of culturally responsive teaching strategies aimed at enhancing students' mathematical understanding and motivation through the incorporation of local cultural heritage.